PLANNING FOR TEACHING AND LEARNING. UNDERSTANDING AND WORKING WITH SYLLABI IN SCHOOLS, LYCEUMS, AND COLLEGES. WHAT GOES INTO LESSON PLANNING AND LESSON PLANS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the essential aspects of planning for teaching and learning with a specific focus on understanding and working with syllabi in schools, lyceums, and colleges. It highlights the importance of aligning lesson planning with curriculum goals and learners’ needs. It examines the importance of systematic lesson planning, the structural elements of a syllabus, and the pedagogical principles guiding the development of effective lesson plans.